A Waitlist-Controlled Trial of Behavioral Parent Training for Fathers of Preschool Children. Issue 2 (3rd April 2018) - Caserta, Abigail; Fabiano, Gregory A.; Hulme, Karen; Pyle, Kellina; Isaacs, Lesthia; Jerome, Stephanie
ABSTRACT: Positive father involvement is an express goal of early childhood programs, including Head Start, because fathers can develop positive parenting strategies that may help improve child and family functioning. The goal for this study was to adapt a clinic-based, behavioral parent training program previously used for fathers of children with attention deficit/hyperactivity disorder to be used in an after-school format for young children at risk for academic or behavioral challenges. In a pilot study, 67 fathers were randomly assigned to the behavioral parent training program, or a waitlist, and at the end of the initial 6 weeks of the program all fathers participated in a parent–child interaction to evaluate parenting behavior. Results indicated that fathers who received the behavioral parenting program were less negative in their interactions with their child, in spite of inconsistent attendance at the program overall. Fathers did not evidence improved rates of praise or modify their rates of using commands. Results indicated that the behavioral parent training program was successfully implemented as an after-school program for young children, and that it may help support reductions in negative and coercive parent–child interactions.